Short-Run Pain, Long-Run Gain : The Effects of Financial Liberalization - Schmukler, Sergio (IMF Working Papers; Working Paper ;, 2003)
We examine the short- and long-run effects of financial liberalization on capital markets. To do so, we construct a new comprehensive chronology of financial liberalization in 28 mature and emerging market economies since 1973. We also construct an algorithm to identify booms and busts in stock market prices. Our results indicate that financial liberalization is followed by more pronounced boom-bust cycles in the short run. However, financial liberalization leads to more stable markets in the long run. Finally, we analyze the sequencing of liberalization and institutional reforms to understand the contrasting short- and long-run effects of liberalization.